2018
DOI: 10.1182/blood-2017-06-741041
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy targeting 4-1BB: mechanistic rationale, clinical results, and future strategies

Abstract: 4-1BB (CD137, tumor necrosis factor receptor superfamily 9) is an inducible costimulatory receptor expressed on activated T and natural killer (NK) cells. 4-1BB ligation on T cells triggers a signaling cascade that results in upregulation of antiapoptotic molecules, cytokine secretion, and enhanced effector function. In dysfunctional T cells that have a decreased cytotoxic capacity, 4-1BB ligation demonstrates a potent ability to restore effector functions. On NK cells, 4-1BB signaling can increase antibody-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
394
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(401 citation statements)
references
References 104 publications
7
394
0
Order By: Relevance
“…S2F), which suggested that despite similar levels of activation, 4–1BB protein expression differed based on genotype. Since 4–1BB is currently tested as a co-stimulatory cancer immunotherapy target (Chester et al, 2018), our description of genotype-dependent effects on expression of 4–1BB in T cells may aid in the development of genetic biomarkers that stratify potential responders to 4–1BB targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…S2F), which suggested that despite similar levels of activation, 4–1BB protein expression differed based on genotype. Since 4–1BB is currently tested as a co-stimulatory cancer immunotherapy target (Chester et al, 2018), our description of genotype-dependent effects on expression of 4–1BB in T cells may aid in the development of genetic biomarkers that stratify potential responders to 4–1BB targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Costimulatory receptors of the Ig superfamily tend to activate phosphatidylinositol 3-kinase (PI3K) leading to protein kinase B (Akt) and downstream nuclear factor jB (NF-jB) activation, while TNFR superfamily members preferentially recruit and activate TNF receptorassociated factors (TRAFs) to potentiate NF-jB activation. 3,6 However, activation of costimulatory receptors can lead to unbridled inflammatory responses with life-threatening consequences. The degree of costimulation received by a T cell is modulated by T cell surface expression of costimulatory molecules, expression of their ligands on APCs and T cell expression of co-inhibitory receptors, many of which compete with costimulatory receptors for the same ligands.…”
Section: T Cell Costimulationmentioning
confidence: 99%
“…The CAR T cells lacking a CD28 costimulatory domain showed limited expansion and poor persistence, whereas the T cells expressing a CAR incorporating the CD28 domain underwent a greater degree of expansion and persisted for longer in all six patients. 6 A TNFR superfamily member, 4-1BB, is expressed on a subset of resting CD8 + T cells and is upregulated on both CD4 + and CD8 + T cells following activation. 11,29,30 4-1BB (CD137) 4-1BB (TNFRSF9, CD137) is an activation-induced T cell costimulatory molecule, first described in 1989.…”
Section: Cd28mentioning
confidence: 99%
“…CD137, a representative costimulatory molecule belong to TNF‐receptor superfamily, is an important target for tumor immunotherapy . Its gene expression is inducible in activated T cells .…”
Section: Introductionmentioning
confidence: 99%